Sovereign spreads, central bank collateral frameworks, and periphery premia in the Eurozone - Florian Schuster (Dezernat Zukunft e.V., 2023)
This paper studies the emergence of sovereign bond yield spreads in the Eurozone prior to the financial crisis. While spreads were close to zero in European government debt markets until the mid-2000s, they have persistently widened since then in many member states. We employ a difference-in-differences approach to analyze this phenomenon. We find that the Eurosystem's move from unconditional to conditional collateral eligibility of sovereign bonds, as part of the 2005 Single List reform, was the institutional change triggering the emergence of sovereign spreads in the Euro Area. Conditional eligibility becomes effective predominantly through a periphery premium: higher yields have been demanded from countries whose business cycles deviate most from the average Eurozone cycle. In contrast, spreads did not arise in response to adverse macroeconomic and fiscal fundamentals.
Keywords: 330